Adiposity and Leukocyte Telomere Length in US Adults by Sex-Specific Race/Ethnicity: National Health and Nutrition Examination Survey - Davis, Sharon K. (Ethn Dis, 2020)
OBJECTIVE: Little is known about the relationship between adiposity and telomere length in the United States population. The objective of our research was to examine this relationship in a representative, socioeconomically and sex-specific, diverse racial/ethnic population in the United States. METHODS: Body mass index (BMI), % total body fat (TBF) and waist circumference (WC) with leukocyte telomere length (LTL) were examined according to sex-specific race/ethnicity using separate adjusted multivariate linear regressions on a sample of 4,919 respondents aged 20-84 years from the National Health and Nutrition Examination Survey’s 1999-2002 data. RESULTS: LTL was shortened .41%, .44%, and .16% in African American (AA) women and was associated with increasing BMI, %TBF, and WC, (β:-.0041, 95%CI: -.0070, -.0012; P=.007; β:-.0044, 95% CI: -.0081, -.0007; P=.02; β:-.0016, 95%CI: -.0031, -.0001; P=.04, respectively). LTL was shortened .29% in White women and was associated with increasing %TBF (β:-.0029, 95%CI: -.0048, -.0009; P=.006). There were no associations among AA men, White men or Mexican American men and women. CONCLUSIONS: LTL is associated with an obesity phenotype in AA women. Tailored intervention is needed to ameliorate the burden of excess adiposity and subsequent cellular aging.